Literature review: Pengaruh Pemilihan Kosmetik terhadap Kesehatan Kulit - Anik Maghfiroh; Rayya Salsabil; Taqiya Cantika As Salma; Sherly Clarah Wulan Dary; Faradina Utami; Fayza Navisya Rayya (Lembaga Pengembangan Kinerja Dosen, 2026)
The increasing use of facial cosmetics among adolescents and young adults is not always accompanied by adequate cosmetic literacy, potentially leading to skin health problems. Many consumers choose products based on trends without understanding their skin type, ingredients, and safety aspects, which can lead to skin barrier damage, irritation, and long-term dermatological disorders. This study aims to analyze the influence of cosmetic choices on facial skin health through a literature review. The method used was a qualitative literature study with a purposive sampling technique of scientific articles published between 2015 and 2025 that were relevant to the behavior of adolescents and young adults and the impact of cosmetic ingredients on the skin. Data were analyzed using content analysis to identify the relationship between knowledge, attitudes, and cosmetic choices. The results show that cosmetic knowledge tends to be high, but is not always followed by appropriate selection behavior, with varying correlation strengths. These findings confirm that cosmetic literacy contributes to the tendency to choose more appropriate products, but is not the sole determining factor. Therefore, education is needed that emphasizes cognitive aspects while fostering critical attitudes in choosing cosmetics safely and responsibly.